MCL-1 (myosin light chains-1) in differential diagnosis of dyspnea - Stejskal, David; Lačňák, Bořek; Andělová, K; Škvařilová, Marcela; Bartek, Josef (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
Myosin light chains-1 (MLC-1) have been recently associated with the markers of heart function (NYHA, LVEF, NT-proBNP). Verification of the relationship between markers of heart function (New York Heart Association classification (NYHA), left ventricle ejection fraction determination (LVEF), N terminal prohormone of natriuretic peptide B type BNP (NT-proBNP) and concentrations of myosin light chains-1 (MLC-1) was assessed. Patients examined for dyspnea without signs of acute coronary syndrome. All patients underwent echocardiography (calculation of left ventricle ejection fraction--LVEF) and in the serum of all subjects NT-proBNP (ELEIA) and MLC-1 (ELISA) were determined. In the 38 patients (21 men, 17 women), mean age of 58 years (+/-12 years as 1 SD), a significant negative correlation was found between NT-proBNP and LVEF (r = - 0.47; p = 0.02, Spearman). The median levels of NT pro-BNP were closely associated with NYHA classification (type II--584 ng/l, type III--2792 ng/l, type IV--6400 ng/l; p < 0.05). Individuals with clinical NYHA IV differed significantly in median MLC-1 concentrations from persons with clinical NYHA classification II and III (type II--5.7 ng/l, type III--8.9 ng/l, type IV--17 ng/l; p < 0.05). A significant negative correlation between MLC-1 and LVEF (-0.35; p < 0.03) and significant positive correlations between MLC-1 and NT-proBNP (0.42; p < 0.012) were found. In conclusion MLC-1 cannot be used as a diagnostic marker in differential diagnosis of dyspnea.
Keywords: tepový objem; Stroke Volume; Humans; Natriuretic Peptide, Brain; diferenciální diagnóza; lidé středního věku; Middle Aged; Sensitivity and Specificity; Peptide Fragments; mužské pohlaví; lehké řetězce myosinu; ROC Curve; Diagnosis, Differential; dyspnoe; natriuretický peptid typu B; peptidové fragmenty; srdeční selhání; biologické markery; ženské pohlaví; Myosin Light Chains; ROC křivka; lidé; senzitivita a specificita; Dyspnea; Biomarkers; Heart Failure; Male; Female